Different types of sounds influence gaze differently in videos - Guanghan Song; Denis Pellerin; Lionel Granjon (Journal of Eye Movement Research)
This paper presents an analysis of the effect of different types of sounds on visual gaze when a person is looking freely at videos, which would be helpful to predict eye position. In order to test the effect of sound, an audio-visual experiment was designed with two groups of participants, with audio-visual (AV) and visual (V) conditions. By using statistical tools, we analyzed the difference between eye position of participants with AV and V conditions. We observed that the effect of sound is different depending on the kind of sound, and that the classes with human voice (i.e. speech, singer, human noise and singers) have the greatest effect. Furthermore, the results of the distance between sound source and eye position of the group with AV condition, suggested that only particular types of sound attract human eye position to the sound source. Finally, an analysis of the fixation duration between AV and V conditions showed that participants with AV condition move eyes more frequently than those with V condition.